Penyuluhan Pendidikan Kesetaraan di RT 01 Desa Tanjung Batu Kecamatan Tenggarong Seberang Kabupaten Kutai Kertanegara - Fauziah, Anisa; Tufa, Istifadah Hardhea; Wati, Syahidah Sandya; Amanda, Reygina; Khairunnisa, Rizka Tri; Afrizal, Riski; Safitri, Febiyana; Luthfiana, Bika Nisa; Alisalman, Muhamad (Nawadeepa: Jurnal Pengabdian Masyarakat, 2022)
The problem that occurs in RT OI Tanjung Batu Village is that the majority of the population with formal education only reaches the junior high school level and the high number of dropouts. Therefore, the implementation of equality education counseling is very appropriate to do. The method used in this activity is the lecture and discussion method. The preparatory phase begins with observation, interviews and coordination with RT 01 apparatus. Making an agreement on extension activities with RT 01 apparatus, preparing learning media in the form of materials and videos. Equality education extension activities were carried out in December with 15 participants from RT 01 Tanjung Batu Village. In the implementation of counseling, it is carried out by delivering material with lectures. Then the discussion with the participants. The result is that the people of RT 01 have new knowledge about equality education and its benefits.